2013
DOI: 10.1128/iai.00982-12
|View full text |Cite
|
Sign up to set email alerts
|

Novel Cholix Toxin Variants, ADP-Ribosylating Toxins in Vibrio cholerae Non-O1/Non-O139 Strains, and Their Pathogenicity

Abstract: e Cholix toxin (ChxA) is a recently discovered exotoxin in Vibrio cholerae which has been characterized as a third member of the eukaryotic elongation factor 2-specific ADP-ribosyltransferase toxins, in addition to exotoxin A of Pseudomonas aeruginosa and diphtheria toxin of Corynebacterium diphtheriae. These toxins consist of three characteristic domains for receptor binding, translocation, and catalysis. However, there is little information about the prevalence of chxA and its genetic variations and pathogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
91
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(96 citation statements)
references
References 52 publications
4
91
0
1
Order By: Relevance
“…However, these strains harbored other virulence genes similar to non-O1/non-O139. Both chxA and TTSS genes were frequently found among non-O1/non-O139 pathogenic strains and associated with diarrhea [36, 51, 55]. However, the environmental O1 strains in this study harbored chxA gene (TC22) and TTSS (MK14), indicating virulence potential to cause disease.…”
Section: Discussionmentioning
confidence: 68%
“…However, these strains harbored other virulence genes similar to non-O1/non-O139. Both chxA and TTSS genes were frequently found among non-O1/non-O139 pathogenic strains and associated with diarrhea [36, 51, 55]. However, the environmental O1 strains in this study harbored chxA gene (TC22) and TTSS (MK14), indicating virulence potential to cause disease.…”
Section: Discussionmentioning
confidence: 68%
“…Given that the environment is dominated by non-O1/non-O139 strains, this observation suggests that these virulence factors probably do not promote fitness in the aquatic niche although there is some data that challenges this conclusion for at least chitin binding lectins (Kirn et al 2005). Various typing methods and deep sequencing has enabled more sensitive surveillance of CTX–ϕ in strains isolated from the environment (Rivera et al 2001; Singh et al 2001; Pang et al 2007; Awasthi et al 2012; Hasan et al 2012; Sealfon et al 2012; Sellek et al 2012). The prevalent assumption that the presence of toxigenic strains in water provides proof that toxigenic strain occupy a stable environmental niche needs to be readdressed with modern methods that might differentiate between contamination of the environment by nearby cholera victims as opposed to these strains maintaining themselves within the environment in the absence of infected humans.…”
Section: Conventional Genomics and Established Virulence Islandsmentioning
confidence: 99%
“…While most of these putative virulence factors are expressed in only a fraction of clinical NOVC isolates, RTX, HapA and VCC are expressed in almost all V. cholerae serogroups and are therefore more promising as potential toxigenic factors [2], [9], [11]. VCC is a particularly interesting candidate; in a study using a streptomycin-fed murine model of disease, VCC was shown to be the predominant cause of death [12].…”
Section: Introductionmentioning
confidence: 99%